2018
DOI: 10.1016/j.dib.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cassava mosaic disease and associated whitefly vectors in South West and North Central Nigeria: Data exploration

Abstract: Cassava mosaic disease (CMD) is one of the most economically important viral diseases of cassava, an important staple food for over 800 million people in the tropics. Although several Cassava mosaic virus species associated with CMD have been isolated and characterized over the years, several new super virulent strains of these viruses have evolved due to genetic recombination between diverse species. In this data article, field survey data collected from 184 cassava farms in 12 South Western and North Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The impact of climate change on the occurrence of whitefly populations has also been explored recently with a consistent relationship between B. tabaci abundance and suitable climatic conditions [ 58 ]; the increasing climate suitability in parts of East and Central Africa across the 39 years of the study shows a correlation not only with the increased prevalence of B. tabaci but also the devastating viruses transmitted by these whiteflies [ 58 ]. Of great concern presently is that West Africa, the major cassava-producing region in sub-Saharan Africa [ 59 ], has not yet witnessed superabundant populations despite this region having similar cassava mosaic begomoviruses and whitefly populations to those reported in East Africa [ 18 , 60 , 61 , 62 ]. Unravelling the factors contributing to the high whitefly populations in East Africa is of paramount importance to enable the development of whitefly management practices to prevent similar increases in whitefly abundance occurring in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of climate change on the occurrence of whitefly populations has also been explored recently with a consistent relationship between B. tabaci abundance and suitable climatic conditions [ 58 ]; the increasing climate suitability in parts of East and Central Africa across the 39 years of the study shows a correlation not only with the increased prevalence of B. tabaci but also the devastating viruses transmitted by these whiteflies [ 58 ]. Of great concern presently is that West Africa, the major cassava-producing region in sub-Saharan Africa [ 59 ], has not yet witnessed superabundant populations despite this region having similar cassava mosaic begomoviruses and whitefly populations to those reported in East Africa [ 18 , 60 , 61 , 62 ]. Unravelling the factors contributing to the high whitefly populations in East Africa is of paramount importance to enable the development of whitefly management practices to prevent similar increases in whitefly abundance occurring in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…For plants exhibiting CMD symptoms, symptom severity was scored following previously described methods [2] . CMD symptom severity was scored on a scale of 1–5 as previously described [ 3 , 4 ]. CMD incidence was calculated as the proportion of sampled plants showing CMD symptoms.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The AnSL1 and AnSL2 biotypes (SSA3) were the only biotypes reported on cassava in the study [29]. More recently, two surveys have been reported that detail the distribution of whiteflies in south-western [31,42] and north-central Nigeria [42]. The surveys in the region reported up to 35 whitefly species including B. tabaci and B. afer.…”
Section: Introductionmentioning
confidence: 91%